The Drought and Food Crisis in the Horn of Africa : Impacts and Proposed Policy Responses for Kenya - World Bank (Washington, DC, 2017)
This policy note provides an assessment of some of the impacts and proposed policy responses to problems related to the drought, including the rise in food prices. To address immediate needs, the humanitarian response to the drought is being managed by the Government of Kenya and a number of international organizations including the World Food Program (WFP), the Food and Agriculture Organization (FAO), and the United Nations Children's Fund (UNICEF). Recognizing that response needs are currently recognizing that response needs are currently being addressed, this note focuses on policy changes that can address long term vulnerabilities related to the drought.